Cost-effectiveness of the 13-valent pneumococcal conjugate vaccine in adults in Portugal versus "no vaccination" and versus vaccination with the 23-valent pneumococcal polysaccharide vaccine. Issue 4 (3rd April 2019) - Gouveia, Miguel; Jesus, Gonçalo; Inês, Mónica; Costa, João; Borges, Margarida
ABSTRACT: The burden of pneumococcal disease in adults is substantial from a social and economic point of view. This study assessed the cost-effectiveness of the 13-valent pneumococcal conjugate vaccine (PCV13) for the prevention of invasive pneumococcal disease and pneumococcal pneumonia in adults versus "no vaccination" and versus vaccination with the 23-valent pneumococcal polysaccharide vaccine (PPSV23). A Markov model was used to simulate three strategies: no vaccination, complete vaccination with PPSV23 and complete vaccination with PCV13. The comparison between strategies allowed the estimation of clinical and economic outcomes including incremental cost-effectiveness ratios (ICER) and incremental cost-utility ratios (ICUR). The model took into account the distributions of age, risk profile, vaccination status, type of immunization and time since vaccination in the population. A societal perspective was adopted and a lifetime horizon was considered. Different sources of data and assumptions were used to calibrate PPSV23 and PCV13 effectiveness. Inpatient costs were based on the 2013 diagnosis-related group (DRG) database for National Health Service (NHS) hospitals and expert opinion; NHS official tariffs were the main source for unitary costs. PCV13 shows ICURs of €17, 746/QALY and €13, 146/QALY versus "no vaccination" and vaccination with PPSV23, respectively. Results proved to be robust in univariate sensitivity analyses, where all ratios were below a €20, 000 threshold, with the exception of the scenario with PCV13 effectiveness halved. In a probabilistic sensitivity analysis, 94% of simulations showed cost-effectiveness ratios lower than €20, 000/QALY, in both strategies. It was found that PCV13 is a cost-effective strategy to prevent pneumococcal disease in adults in Portugal.